Clinical and pathological implications of the presence of MECA-79-expressing tumor cells in pathological stage IA lung adenocarcinoma - Tomohito Saito; Mitsuaki Ishida; Tomoya O. Akama; Shiho Hattori; Natsumi Maru; Takahiro Utsumi; Aki K. Kobayashi; Kento J. Fukumoto; Hiroshi Matsui; Yohei Taniguchi; Yoshinobu Hirose; Katsuyasu Kouda; et al. (PLoS ONE, 2025)
Approximately 15% of patients with resected pathological stage IA lung adenocarcinoma develop recurrent disease, indicating the formation of a cancer metastasis-promoting microenvironment, and highlighting the importance of identifying early prognostic biomarkers. The MECA-79 epitope is a glycan structure modulating immune response, normally expressed on high endothelial venules. Ectopic MECA-79 expression has been recently reported in several cancer cells and is associated with poor prognosis. In this retrospective cohort study, we aimed to investigate the clinical and pathological significance of tumoral MECA-79 expression in early-stage lung cancer. Immunohistochemical analysis for MECA-79 was performed in 195 patients with pathological stage IA lung adenocarcinoma undergoing lobectomy. Clinical, radiological, and pathological factors were assessed, and recurrence-free survival (RFS) was analyzed using Kaplan–Meier analysis and univariable Cox regression proportional hazards models. Multivariable Cox analyses were performed as exploratory analyses only due to the limited number of recurrence events. Tumoral MECA-79 expression was observed in 5.1% of cases (n = 10). Patients with MECA-79+ tumor cells exhibited a larger pathological invasive size (2.1 vs. 1.6 cm, P = 0.044), higher rates of vascular invasion (90.0% vs. 40.0%, P = 0.0023), and increased 5-year postoperative recurrence (40.0% vs. 7.6%, P = 0.0061). Kaplan–Meier analysis demonstrated significantly worse RFS for patients with MECA-79+ tumor cells (5-year rate: 54.9% vs. 87.4%, P = 0.003). The univariate Cox regression model identified body mass index, histological grade based on the International Association for the Study of Lung Cancer histological grading system, vascular invasion, spread through air spaces, and the presence of MECA-79+ tumor cells as prognostic factors. Our results indicate that tumoral MECA-79 expression is associated with the recurrence of resected pathological stage IA lung adenocarcinoma; however, these findings should be validated in multicenter, stage-matched cohorts.